PERBANDINGAN KINERJA REKSADANA SYARIAH SAHAM DENGAN KINERJA PASAR (ISSI) DI BURSA EFEK - Nur Kholidah (STAI Syubbanul Wathon Magelang, 2018)
The purpose of this study is to determine whether there is a differencebetween the performance of sharia mutual fund shares with marketperformance by using the Sharpe Method, Treynor, TT Index andMM Index. This study is comparative, IE compares the return rate ofsharia mutual fund shares with ISSI index return as a benchmark.The samples taken there are 7 sharia mutual fund shares of the totalpopulation of 85 sharia mutual fund shares during the study period.The data used are NAV/investment units of each sharia mutual fundshares, SWBI, and ISSI return. The data are in the form of daily datafor 6 months, from October 1, 2015 to March 2016. The results of thisstudy indicate that the Shariah mutual fund performance measured bythe Sharpe method during the period October 2015 to March 2016 hasa positive performance. Shariah mutual fund performance measuredby the Treynor method during the period October 2015 to March 2016has 6 positive Treynor values and 1 negative Treynor value. Shariamutual fund performance measured by the TT index method duringthe period October 2015 to March 2016 has 6 positive TT index valuesand 1 negative TT index value. Sharia mutual fund performancemeasured by MM index method during period of October 2015 untilMarch 2016 has MM index positive value, but the return is smallerthan market performance return (ISSI).